2017
DOI: 10.1155/2017/1925820
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of Potential Baker’s Yeast from Indigenous Resources of Nepal

Abstract: The study aims to isolate the yeast strains that could be used effectively as baker's yeast and compare them with the commercial baker's yeast available in the market of Nepal. A total of 10 samples including locally available sources like fruits, Murcha, and a local tree "Dar" were collected from different localities of Bhaktapur, Kavre, and Syangja districts of Nepal, respectively. Following enrichment and fermentation of the samples, 26 yeast strains were isolated using selective medium Wallerstein Laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…The capability of fermentation was assessed by observing the colour change in the medium after the incubation. Sugar fermentation was observed by the colour change from red to yellow due to acid production [16].…”
Section: Physiologicalmentioning
confidence: 99%
“…The capability of fermentation was assessed by observing the colour change in the medium after the incubation. Sugar fermentation was observed by the colour change from red to yellow due to acid production [16].…”
Section: Physiologicalmentioning
confidence: 99%
“…Then it was incubated at 27 o C for 7 days. The fermentation medium was put in a test tube equipped with a Durham tube [6]. A positive reaction for fermentation was indicated by a change in the media from red to pink followed by the formation of bubbles in the Durham tube.…”
Section: Carbohydrate Fermentation Testmentioning
confidence: 99%
“…Yeast has four roles in the bread-making process, namely to increase the volume of the dough due to the formation of carbon dioxide during the fermentation process, to develop the structure and texture of the dough due to stretching by the expansion of CO2 gas bubbles, to improve the taste and to add some nutritional value to the bread [4]. Yeast for bread developers must have basic requirements, namely being able to survive in conditions that have high ethanol levels between 10%-15%, and tolerance to various temperature conditions of 25 o C, 30 o C, 37 o C dan 45 o C [6]. Good yeast as a developer Bread must be able to form flocculants or floc deposits in the flocculation process and not produce hydrogen sulfide (H2S) gas which is a compound that forms a foul smell and bad taste in bread processing [2].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, commercial yeast can be obtained from baker's yeast and tapai yeast. Other research has reported that tapai yeast contains molds, such as Rhizopus oryzae, Monilesaurus rouxii, Aspergillus orzae, Saccharomyces cervisiae, Endomycopsis burtonii, Pediococcus pentosaceus, Hansenula anomala, Candida krusei, Candida magnoliae (Chiang et al 2006;Rahman et al 2018), whereas baker's yeast contains Saccharomyces cerevisiae (Karki et al 2017). Kumoro et al (2012) used baker's yeast in the production of jackfruit wine.…”
Section: Introductionmentioning
confidence: 99%